Acidity decline in Antarctic ice cores during the Little Ice Age linked to changes in atmospheric nitrate and sea salt concentrations. Issue 9 (13th May 2014) - Pasteris, Daniel; McConnell, Joseph R.; Edwards, Ross; Isaksson, Elizabeth; Albert, Mary R.
Abstract Acidity is an important chemical variable that impacts atmospheric and snowpack chemistry. Here we describe composite time series and the spatial pattern of acidity concentration (Acy = H+ − HCO3−) during the last 2000 years across the Dronning Maud Land region of the East Antarctic Plateau using measurements in seven ice cores. Coregistered measurements of the major ion species show that sulfuric acid (H2SO4), nitric acid (HNO3), and hydrochloric acid (HCl) determine greater than 98% of the acidity value. The latter, also described as excess chloride (ExCl−), is shown mostly to be derived from postdepositional diffusion of chloride with little net gain or loss from the snowpack. A strong inverse linear relationship between nitrate concentration and inverse accumulation rate provides evidence of spatially homogenous fresh snow concentrations and reemission rates of nitrate from the snowpack across the study area. A decline in acidity during the Little Ice Age (LIA, 1500–1900 Common Era) is observed and is linked to declines in HNO3 and ExCl− during that time. The nitrate decline is found to correlate well with published methane isotope data from Antarctica (δ13CH4), indicating that it is caused by a decline in biomass burning. The decrease in ExCl− concentration during the LIA is well correlated to published sea surface temperature reconstructions in the Atlantic Ocean, which suggests increased sea salt aerosol production associated with greater sea ice extent.